Implementasi Social Media Marketing Sebagai Upaya Meningkatkan Brand Awareness Pada UMKM Keripik Pisang “Dua Putra Putri” Di Desa Karangan - Devina Zulia Rahmatin; Nurul Azizah (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Many resources around the yard of the house are used by the people of Karangan Village to make MSME products, one of which is Mrs. Samilah who produces banana chips. The purpose of this community service is to empower MSME actors by creating work programs, mentoring activities and branding training, as well as social media marketing to increase brand awareness of MSME products